Comparisons of Retinal Nerve Fiber Layer Thickness after Indocyanine Green, Brilliant Blue G, or Triamcinolone Acetonide-Assisted Macular Hole Surgery. (19th May 2014) - Toba, Yoshiharu; Machida, Shigeki; Kurosaka, Daijiro
Abstract : Purpose . To compare the postoperative changes of the retinal nerve fiber layer (RNFL) thickness in patients with macular holes (MHs) treated with vitrectomy with indocyanine green- (ICG-), brilliant blue G- (BBG-), or triamcinolone acetonide- (TA-)assisted internal limiting membrane (ILM) peeling. Methods . Sixty-one eyes of 61 consecutive patients with MHs were studied. Each eye was randomly selected to undergo either ICG- (n = 18 ), BBG- (n = 21 ), or TA-assisted (n = 2 2 ) ILM peeling. The circumferential retinal nerve fiber layer (RNFL) thickness was determined by spectral-domain optical coherence tomography (SD-OCT) before and 1, 3, 6, 9, and 12 months postoperatively. The mean overall and the sectoral thicknesses of the RNFL were obtained for each group. Results . A transient increase of the RNFL thickness was seen in the mean overall and sectoral thicknesses except for the nasal/inferior sector at 1 month after surgery for the three groups. Then, the thickness gradually decreased and returned to the baseline level in all sectors except for the nasal/inferior sector. The differences in the RNFL thickness among the groups were not significant for at least 12 months postoperatively. Conclusions . The degree of change of the RNFL thickness was not significantly related to the type of vital stain used during MH surgery.